Effect of Glycemic Control (HbA1c) on Vitamin B12 Level in Patients with Type 2 Diabetes Mellitus in Babylon City/Iraq - Maha Qasim Abdul Zahra; Prof. Dr. Manal Kamal Rasheed (Academic Journal of Clinicians, 2025)
Background: Vitamin B12 deficiency is a recognized in T2DM patients. Several studies suggest an association between glycemic control and B12 levels. Various studies have shown increased prevalence of vitamin B12 deficiency in patients with type 2 diabetes on Metformin therapy, an antihyperglycemic agent used as first-line treatment for prediabetes and diabetes, might reduce the absorption of vitamin B12 and significantly reduce serum vitamin B12 concentrations. Objectives: To study effect of Glycemic control (HbA1c) on vitamin B12 level in patients with type 2 Diabetes mellitus treated with metformin therapy. Subjects and method: Analytical case control study was conducted from February to October 2024 at private clinic of Diabetes at Babylon city on a total of ninety subjects; thirty healthy controls Hb A1c less than 5.7%), thirty diabetic patients with good glycemic (Hb A1c less than 7%), and thirty diabetic patients with inadequate glycemic control (HbA1c more than 7%). The measurement of HbA1c by A1Care Analyzer, fasting blood sugar by spectrophotometer, vitamin B12 by Fully automated closed system chemiluminescent assay analyzer (MAGLUMI 800 Snibe). Results: Negative correlation between vitamin B12 and HbA1c (r=-0.64, p<0.001), negative correlation with metformin dose (r=-0.66, p<0.001) and negative correlation with metformin duration (r-0.74, p<0.001). Positive correlation between HbA1c and metformin dose (r 0.701 p<0.001) and metformin duration (r 0.78, p<0.001). Positive correlation between metformin dose and metformin duration (r 0.82, p <0.001). Conclusion: In patients with type 2 diabetes mellitus who had been taking metformin; Incidence of vitamin B12 deficiency is high. Vitamin B12 deficiency is correlated closely with metformin dose and duration.Older age is a significant risk factor for vitamin B12 deficiency. Vitamin B12 deficiency is significantly related to inadequate glycemic control